An Analysis of Racism in Uncle Tom’s Cabin from the Marxism Perspective - Jingsai, Ryan (Pakistan Journal of Humanities and Social Sciences, 2023)
Uncle Tom's Cabin is a novel that reflects the cruelty and inhumanity of the slave system. In the novel, Harriet Beecher Stowe created scenes of real artistic power and that her analysis of the capitalistic elements of the slave system were remarkably astute. The racism depicted in this novel is, on the surface, the inhuman oppression and exploitation of black slaves by slave owners. While on the deep level, it is the exploitation and oppression of the proletariat by the bourgeoisie, and this exploitation is a major means for the bourgeoisie to extract the surplus value of working workers. Starting from a Marxism perspective, this article analyzes the economic interests and class relationships behind slavery in the novel, studies the relationship between racism, socio-economic structure, and class contradictions, and explores how racism interweaves with economic interests and becomes a tool of class oppression. While the specter of racism still lingers in American society today, the paper tries to figure out the complexity of racial issues in the United States, thus providing more comprehensive thinking and methods for eliminating racism and inequality in the future.